2013
DOI: 10.2989/16085906.2013.815416
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the potential impact and cost of scaling-up male circumcision in resource poor settings: A case of Uganda

Abstract: This study modelled estimates of the cost and impact of male circumcision (MC) under different scenarios using the Decision Maker's Program Planning Tool on data from Uganda. Results showed that the number of new adult HIV infections could be reduced by 23 000 if MC could be increased from the current 25% to 80% by 2015. The incidence of HIV could be reduced by 0.2 percentage points over the same period. If a scale up programme is to meet a target of 80% by 2015 then the annual number of MCs performed should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This analysis employed primary source facility-level data from Nyanza, Kenya (29 facilities), Namibia (8 facilities), South Africa (9 facilities), Tanzania (18 facilities), Uganda (26 facilities), and Zambia (9 facilities), for a total of 99 facilities (see [5], [6], [9] for detailed discussion of the data including sampling approaches, which varied by country). Data were collected between 2008 and 2011 with samples stratified by geographic region, urban/rural designation, service provider (nongovernmental organization [NGO], public, private), type of facility (hospital, health center, dispensary), and service delivery mode (outreach, campaign, fixed/static).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This analysis employed primary source facility-level data from Nyanza, Kenya (29 facilities), Namibia (8 facilities), South Africa (9 facilities), Tanzania (18 facilities), Uganda (26 facilities), and Zambia (9 facilities), for a total of 99 facilities (see [5], [6], [9] for detailed discussion of the data including sampling approaches, which varied by country). Data were collected between 2008 and 2011 with samples stratified by geographic region, urban/rural designation, service provider (nongovernmental organization [NGO], public, private), type of facility (hospital, health center, dispensary), and service delivery mode (outreach, campaign, fixed/static).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that task shifting of VMMC services does not increase the number of adverse events reported [7], [8] and may actually result in significant cost savings. In Uganda, shifting the procedure from surgeons to medical officers resulted in a savings of 24% [9], while in Namibia shifting the procedure from physicians to surgical nurses reduced the average unit cost by 31% [10]. Finally, two recent studies found that using the alternative non-surgical devices, Shang Ring [11] or PrePex [12], did not result in significant direct cost savings as compared to surgical circumcision.…”
Section: Introductionmentioning
confidence: 99%